2005
DOI: 10.1002/eji.200425823
|View full text |Cite
|
Sign up to set email alerts
|

Tolerant T cells display impaired trafficking ability

Abstract: Based on our previous observation that anergic T lymphocytes lose their migratory ability in vitro, we have proposed that anergic T cells are retained in the site where they have been generated to exert their regulatory function. In this study we have analyzed T lymphocyte trafficking and motility following the induction of tolerance in vivo. In a model of non-deletional negative vaccination to xenoantigens in which dendritic cells (DC) localize to specific lymphoid sites depending on the route of administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Dendritic cells in the GALT present the gut-derived antigens to naïve T cells in Peyer's patches, what results in differentiation of T cells into regulatory T cells (Tregs) producing IL-10 and TGF-β, or internalization of TCR leading to anergy. Thus, orally administered fragments of myelin peptides induce, depending on the antigen dose, active suppression (inhibiting of Th1-dependent immunoresponse) or anergy/clonal deletion of responsive T lymphocytes (both Th1 and Th2) in the mucosal immune system [4,27,40]. Anergic T cells are not able to migrate from the site of tolerance induction, and remaining in the GALT produce anti-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic cells in the GALT present the gut-derived antigens to naïve T cells in Peyer's patches, what results in differentiation of T cells into regulatory T cells (Tregs) producing IL-10 and TGF-β, or internalization of TCR leading to anergy. Thus, orally administered fragments of myelin peptides induce, depending on the antigen dose, active suppression (inhibiting of Th1-dependent immunoresponse) or anergy/clonal deletion of responsive T lymphocytes (both Th1 and Th2) in the mucosal immune system [4,27,40]. Anergic T cells are not able to migrate from the site of tolerance induction, and remaining in the GALT produce anti-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…activation. This has been reported by Mirenda et al [333]. They reported that partial T cell activation can cause T cell unresponsiveness (anergic T cells) due to the defects caused on the T cells migratory ability [333,334].…”
Section: Immunisation By Mannosylated Peptides Resulted In An Impairementioning
confidence: 53%
“…It is also argued that this epitope also bears at least one B cell epitope (323)(324)(325)(326)(327)(328)(329)(330)(331)(332)(333)(334)(335)(336)(337)(338)(339), however, there is only one study that has mentioned the presence of the B cell epitope [327]. In a study by Sun et al, it was shown that 50% of the B cell response generated by the OVA protein was antibody specific to the OVA323-339 epitope [327].…”
Section: Immunisation By Mannosylated Peptides Resulted In An Impairementioning
confidence: 99%
See 2 more Smart Citations